Risk factors and clinical presentation of Stroke in Mukalla, Hadhramout, republic of Yemen: Rasheed Mohammed Bamekhlah , Abdullah Saleh Bin-Nabhan , Nabeel Salim Musaia - جامعة الأندلس للعلوم و التقنية, Rasheed Mohammed Bamekhlah , Abdullah Saleh Bin-Nabhan , Nabeel Salim Musaia (مجلة الأندلس للعلوم التطبيقية, 2023)
Background: Stroke is the third leading cause of death (after heart disease and cancer), and a major cause of long-term disability among survivors. Our country is lacking studies about stroke. Our study aim was to identify the risk factors, clinical presentation and outcome of stroke in our region Hadhramout, Republic of Yemen. Patients and Methods: a retrospective cross-sectional study of stroke patients admitted at Ibnseena Teaching Hospital at Mukalla, Hadhramout, Yemen during the period January 2009- December 2010. Data were collected in a questionnaire from the patients' medical files. Results: there were 774 stroke cases during the study period with age mean of (69±13.3) years; ischemic stroke represented 82.9% and the hemorrhagic type 17.1%. Males were 55.8%. Hypertension was the most common risk factor (57.2%) of cases, followed by diabetes mellitus (44.8%), smoking (20.9%) family history (13.4%), previous attack (10.6%) and dyslipidemia (8.7%). In 4.7% of cases there was no risk factors, 24.5% with one and 70.8% were with ≥2 risk factors. About 75% sake hospital within 24 hours, 90.6% with sudden onset, 61.4% were fully conscious and 38.6% with disturbed consciousness, 22.7% were confused and 15.9% were comatose. Dysphasia was in 31.8%. In-hospital death was 33.6% of cases. About one third of cases died in hospital. Background: Stroke is the third leading cause of death (after heart disease and cancer), and a major cause of long-term disability among survivors. Our country is lacking studies about stroke. Our study aim was to identify the risk factors, clinical presentation and outcome of stroke in our region Hadhramout, Republic of Yemen. Patients and Methods: a retrospective cross-sectional study of stroke patients admitted at Ibnseena Teaching Hospital at Mukalla, Hadhramout, Yemen during the period January 2009- December 2010. Data were collected in a questionnaire from the patients' medical files. Results: there were 774 stroke cases during the study period with age mean of (69±13.3) years; ischemic stroke represented 82.9% and the hemorrhagic type 17.1%. Males were 55.8%. Hypertension was the most common risk factor (57.2%) of cases, followed by diabetes mellitus (44.8%), smoking (20.9%) family history (13.4%), previous attack (10.6%) and dyslipidemia (8.7%). In 4.7% of cases there was no risk factors, 24.5% with one and 70.8% were with ≥2 risk factors. About 75% sake hospital within 24 hours, 90.6% with sudden onset, 61.4% were fully conscious and 38.6% with disturbed consciousness, 22.7% were confused and 15.9% were comatose. Dysphasia was in 31.8%. In-hospital death was 33.6% of cases. About one third of cases died in hospital.